THE ROLE OF THE VILLAGE SECRETARY IN ADMINISTRATIVE ARRANGEMENT IN TOLONDADU I VILLAGE, BOLAANG UKI DISTRICT, SOUTH BOLAANG MONGONDOW REGENCY - Fajri Idong; Wiliam Indra S Mooduto; Siskawaty Yahya (Journal of Economic, Business, and Administration (JEBA), 2024)
The village government apparatus is an institutional capacity of village government that functions to serve the interests of the community/public in the village, the presence of the village secretary has a very crucial role in regulating administration at the village level. Sometimes the placement of village secretaries that are not in accordance with their abilities can result in a decrease in performance, as this research was conducted, namely for the role of the secretary in the arrangement of village administration in Tolondadu 1 Village, Bolaang Uki District, South Bolaang Mongondow Regency. The method used in this study is to use a qualitative design approach because the main focus is on the quality of the analysis, not data that has statistical properties, this research was carried out at the Tolondadu I Village Office, Bolaang Uki District, South Bolaang Mongondow Regency. For 2 months and 2 weeks starting from April 17, 2023 to June 28, 2023. In the study of the Village Secretary, it can be concluded that its performance has a significant influence on the efficiency of public services. It is shown from the results of the interview that the performance of the Village Secretary is considered positive. Recognized as responsive and honest in village management. However, all agreed that further improvements in the education sector and more social programs are needed to help underprivileged families in the villages.